Teaching public speaking in a blended learning environment - Ibrahim, Ainol Haryati; Yusoff, Zailin Shah (International Journal of Social Science and Humanity., 2018)
Information and communication technologies (ICTs) provide new environment for learning and teaching. Today, apart from a fully face-to-face or online environment, blended learning promises opportunities for teaching and learning to be done in both environments. This paper reports results from an analysis of data collected from students at a Malaysian university. An end-of-semester survey was completed by 40 students taking a Public Speaking course. The survey was conducted to understand students’ reactions towards the use of wiki in a blended learning environment. The survey data are being used to inform decisions on the course delivery structure and about adoption of new digital technologies for learning and teaching. Findings from the study indicate that the students found that using wiki facilitated their speech preparation process specifically in receiving feedback and improving speech delivery. Although some had reservation about publishing their speeches publicly on wiki, they understood that it was to their benefit. Therefore using wiki in a blended learning environment was found to be advantageous to the Public Speaking course.